ANALYSIS OF RELATIONSHIP MARKETING TACTICS AT PT. BANK SULUT TUTUYAN - Tololiu, Efiantari (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2013)
Today, most of customers are getting smarter, more informed, and they are free to choose which they would like to take little time to exercise. They can easily defect to competitors who fulfill their expectations. That is why company must have strategy to retain customer loyalty and relationship marketing tactics can be applied to solve this problem. The objectives that expected can be achieved from this study are to analyze relationship marketing tactic based on service quality, price perception, brand image, and communication at PT.BankSulutTutuyan. Theories supporting research are marketing and relationship marketing tactics. The population that is mainly observed in this research is all of the customers of Bank SulutTutuyan with sample of 10 customers as respondents and representative to provide information required in this research. Results and conclusions are most of respondents give positive responses about service quality, price perception, brand image, and communication delivered by employees. Keywords: relationship marketing tactics, service quality, price perception, brand image, communication